Obstetric outcome of induction of labor using prostaglandin gel in patients with previous one cesarean section - Vijayata Sangwan; Sunita Siwach; Pinki Lakra; Mukesh Sangwan; Sanjeet Singh; Rajiv Mahendru (Korean Society of Obstetrics and Gynecology, 2019)
ObjectiveAfter globally acceptance of planned vaginal birth after cesarean section (VBAC), the mode of induction is still a matter of debate and requires further discussion. We aimed to study obstetric outcomes in post-cesarean patients undergoing induction of labor with prostaglandin gel compared with patients who developed spontaneous labor pains.MethodsAll patients at 34 weeks or more of gestation with previous one cesarean section eligible for trial of labor after cesarean section admitted in a labor room within one year were divided in 2 groups. Group one consisted of patients who experienced the spontaneous onset of labor pains and group 2 consisted of patients who underwent induction of labor with prostaglandin gel. They were analyzed for maternofetal outcomes. Descriptive statistics, independent sample t-test, and chi-square test were applied using SPSS 20 software for statistical analysis.ResultsBoth groups were comparable in maternal age, parity, and fetal weight, but different in bishop score, mode of delivery, and neonatal outcome. Admisson bishop score was 6.61±2.51 in group 1 and 3.15±1.27 in group 2 (P<0.005). In the patients who experienced spontaneous labor, 86.82% had successful VBAC. In the patients with induced labor, 64.34% had successful VBAC with an average dose of gel of 1.65±0.75. Both groups had one case each of uterine rupture. The neonatal intensive care unit admission rate was 4.1% in group one and 10.4% in group 2.ConclusionThis study reflects that supervised labor induction with prostaglandin gel in previous one cesarean section patients is a safe and effective option.